Education Module as a Learning Aid for Fantasy-Based Materials via Local Area Network (LAN) - Firmansyah, Ada Udi; Lathifah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Fantasy Education Module is intended to enhance early childhood learning with engaging and interactive learning media. A wireless local area network (LAN) module has been developed for writing, reading and coloring activities to support and enhance classroom productivity. The system provides deeper learning of educational content with multimedia interactive features that can engage younger children in the topics. This paper examines the impact of LAN module design with interactive elements on children’s teaching methods and learning outcomes, concentrating specifically on the role of interactive design in skill development. The study aims to identify the effectiveness of LAN based Module design in improving teaching and learning outcomes with particular attention to how interactive elements can ensure better skill development. The study investigates whether LAN technology, in an interactive environment that supports leisure time, can complement learning spaces better than those traditionally provided. Findings from the primary studies indicate significant learning improvements with more interactive media used, related to cognitive or motor skills. Active participation, and customized learning modes are the themes of the module to meet individual learner styles and task levels. The results of the study show that these modules have great potential as effective educational agents in early childhood education can add much-needed dynamism to basic skills learning.